2021
DOI: 10.17344/acsi.2020.6553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-Ray Crystal Structures and Catalytic Epoxidation of Oxidovanadium(V) Complexes with Aroylhydrazone and Ethyl Maltolate Ligands

Abstract: Two oxidovanadium(V) complexes, [VOL1L] (1) and [VOL2L] (2) (L = ethyl maltolate), derived from the aroylhydrazones 4-bromo-N’-(2-hydroxy-5-methylbenzylidene)benzohydrazide (H2L1) and N’-(3,5-dibromo-2-hydroxybenzylidene)- 4-methoxybenzohydrazide (H2L2), respectively, have been synthesized and characterized by elemental analysis, infrared and electronic spectroscopy. Structures of the complexes were further confirmed by single crystal X-ray determination. The V atoms in the complexes are coordinated by the ONO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(6 reference statements)
1
0
0
Order By: Relevance
“…In this sense, the formation of peroxy-vanadium(V) species in the epoxidation mechanism showed that only the reactions using CHCl 3 and CCl 4 as solvents provided viable conversion rates. This is also reported with vanadium(V) complexes [77,78] including a tridentate ONO aroylhydrazone ligand using a solvent mixture of CH 3 OH/CH 2 Cl 2 . With solvent effect studies, the best epoxidation results were found by Grivani with CHCl 3 as solvent and TBHP as an oxidizing agent, presenting a conversion ratio of 84%.…”
Section: Current Overviewsupporting
confidence: 63%
“…In this sense, the formation of peroxy-vanadium(V) species in the epoxidation mechanism showed that only the reactions using CHCl 3 and CCl 4 as solvents provided viable conversion rates. This is also reported with vanadium(V) complexes [77,78] including a tridentate ONO aroylhydrazone ligand using a solvent mixture of CH 3 OH/CH 2 Cl 2 . With solvent effect studies, the best epoxidation results were found by Grivani with CHCl 3 as solvent and TBHP as an oxidizing agent, presenting a conversion ratio of 84%.…”
Section: Current Overviewsupporting
confidence: 63%